Analyzing Short-run and Long-run Causality Relationship among CO2 Emission, Energy Consumption, GDP, Square of GDP, and Foreign Direct Investment in Environmental Kuznets Curve for Thailand - Bunnag, Tanattrin (International Journal of Energy Economics and Policy, 2023)
This paper analyzes the causal link between CO2 emission, energy consumption, GDP, square of GDP, and foreign direct investment in the Environmental Kuznets Curve for Thailand from 1971-2014. Three steps are used: bound tests to verify the presence of cointegration, autoregressive distributed lag (ARDL) model to check the effects of the dependent variables on the independent variable in the short run and long run, and finally, the vector error correction (VECM) was used the detect the causal relationships among variables. The results show no cointegration between variables, confirming the short-run relationship's existence. In addition, the Granger causality results show varied outcomes, indicating that two bidirectional causal relationships exist in the short run. The first relationship is between energy consumption and GDP, and the second is between energy consumption and GDP2. In addition, there are seven unidirectional relationships where FDI affects CO2 emission, energy consumption, GDP, and GDP2, including CO2 emission affects energy consumption, GDP, and GDP2. The results of long-run causal relationships show three bidirectional causal relationships between GDP and CO2 emission, GDP2 and CO2 emission, including GDP and GDP2. Moreover, there are two unidirectional relationships: GDP influences energy consumption and GDP2 affects energy consumption. Therefore, in terms of policy, the Thai government should support using more renewable energy. Including foreign direct investment, the government should issue a policy for foreign investors' investment by regulating green factories and efficient technology in reducing pollution emissions.